Clustering of Brown Planthopper Biotype Based on RAPD-PCR - BAHAGIAWATI BAHAGIAWATI; HABIB RIJZAANI (Bogor Agricultural University, Indonesia, 2005)
Random amplified polymorphic DNA (RAPD) technique was used to differentiate two brown planthopper biotypes, that were multiplied in the greenhouse. Ten selected random decamer RAPD primers produced unique DNA band patterns for each individual brown planthopper. However, no single primer produced DNA band that could differentiate the two brown planthopper biotype populations. Nonetheless, analysis of the DNA band patterns was able to cluster the majority of the individual samples according to their respective biotypes. Molecular data analysis also indicated greater genetic variation within biotype population than among biotypes.